2016
DOI: 10.1163/1568539x-00003393
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation in brain gene expression profiles of aggressive and nonaggressive individual sticklebacks

Abstract: Within many species, some individuals are consistently more aggressive than others. We examine whether there are differences in brain gene expression between aggressive versus nonaggressive behavioural types of individuals within a natural population of male three-spined sticklebacks (Gasterosteus aculeatus). We compared gene expression profiles of aggressive male sticklebacks to nonaggressive males in four regions of the brain (brainstem, cerebellum, diencephalon and telencephalon). Relatively few genes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 70 publications
(87 reference statements)
2
27
0
Order By: Relevance
“…; Bell et al. ) and honey bees (Alaux et al. ), and have ascribed a strong and multigenic transcriptional basis to behavioral variation.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…; Bell et al. ) and honey bees (Alaux et al. ), and have ascribed a strong and multigenic transcriptional basis to behavioral variation.…”
mentioning
confidence: 99%
“…), though one study has found transcriptional overlap between behavioral transitions and behavioral variation in sticklebacks (Bell et al. ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to having a fully sequenced genome, they have been used in comparative cross-taxa studies looking for a conservation in the molecular underpinnings of social behavior (Rittschof et al 2014; Saul et al 2019) with both emerging and classic model systems. Indeed, there are already hundreds of previously identified candidate genes for social behavior waiting to be characterized (Sanogo et al 2011; Laine et al 2012; Greenwood et al 2013; Mommer & Bell 2014; Greenwood & Peichel 2015; Bell et al 2016; Bukhari et al 2017) and well-established behavioral assays (van Iersel 1953; Rowland 1982) that are amenable to automation (Ardekani et al 2013; Norton & Gutiérrez 2019).…”
Section: Introductionmentioning
confidence: 99%